Awareness of disease and self care among hypertensive patients attending Tribhuvan University Teaching Hospital, Kathmandu, Nepal - Bhandari, Buna; Bhattarai, Mahesh; Bhandari, Manjul; Jha, Nilambar (Journal of Nobel Medical College, 2012)
Background: Hypertension (HTN) is a major risk factor for cardiovascular and renal diseases. The prevalence of hypertension has substantially increased during the past four decades. Information on prevalence as well as awareness regarding treatment and prevention of hypertension is scarce particularly in rural settings. The levels of awareness, treatment, and control of HTN vary between different countries and population groups. Objectives: The objective of this study was to find out the awareness of hypertensive patients about their own disease and self care. Methodology: Descriptive cross sectional study was conducted among 50 hypertensive patients who were admitted to Tribhuvan University Teaching Hospital (TUTH) and attended to medical OPD. Data was collected by using interview schedule by face to face interview method. Results: Among 50 hypertensive patients, 56% were aware about meaning of hypertension, 68% symptoms, 34% cause, 62% prognosis, and 62% complication of HTN. Likewise regarding self care, 70% were doing regular follow up, 92% using regular medication, most of them (80%) were not smoker and 84% were non alcoholic, and 74% taking low fat and low salt diet. Conclusion: Study finding reflects many of them (56%) had more than 50% of knowledge about the hypertension and more than half (54%) were giving more than 50% emphasis about their own self care. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7296 Journal of Nobel Medical College (2012), Vol.1 No.2 p.29-35